2020
DOI: 10.1080/13670050.2020.1829538
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the IELTS test: Chinese and Japanese postgraduate UK experiences

Abstract: This case study explores the challenges that Master's students encounter when learning to write in academic English as part of a UK postgraduate course, after having achieved the required IELTS entry score. Interviews with six Chinese and Japanese learners at different stages of the Master's study revealed more sophisticated writing difficulties than they had previously experienced. Although students were largely managing their written work overall, there were recurring challenges with critical thinking, the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 36 publications
(40 reference statements)
1
21
0
Order By: Relevance
“…Paul then concluded that IELTS scores were not adequate representation of students' ability to handle more sophisticated tasks specific to their respective disciplines, and stated that the correlation between IELTS Writing band scores and success in completing academic tasks remained unclear. Similarly, Clark and Yu (2020) uncovered that Japanese and Chinese Master's students in the UK found written university assignments much more sophisticated than IELTS writing tasks. In particular, they professed that academic writing tasks demand high levels of critical thinking, the use of readings as reference and the ability to present evidence and deliver a clear message, as opposed to IELTS writing which puts greater emphasis on lexical and grammatical range.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Paul then concluded that IELTS scores were not adequate representation of students' ability to handle more sophisticated tasks specific to their respective disciplines, and stated that the correlation between IELTS Writing band scores and success in completing academic tasks remained unclear. Similarly, Clark and Yu (2020) uncovered that Japanese and Chinese Master's students in the UK found written university assignments much more sophisticated than IELTS writing tasks. In particular, they professed that academic writing tasks demand high levels of critical thinking, the use of readings as reference and the ability to present evidence and deliver a clear message, as opposed to IELTS writing which puts greater emphasis on lexical and grammatical range.…”
Section: Resultsmentioning
confidence: 99%
“…To maintain a high degree of authenticity, the first iteration of the IELTS academic test was offered with three specialized modules in Reading and Writing to cater for candidates' selected courses of study (Clapham & Alderson, 1997;Davies, 2008). However, limited success and administrative issues prompted the IELTS test makers to revise and generalize the test (Clapham, 1996), which consequently made it less authentic (Coombe et al, 2012) and thus disadvantageous for students from less relevant disciplines (Clark & Yu, 2020). Nevertheless, this trade-off between practicality and authenticity was deemed acceptable, since attempts to introduce subject-specific modules have failed and been left out of the current IELTS version (Charge & Taylor, 1997).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ese tests nowadays play a crucial role in many people's lives. ey are used for making critical decisions, such as admissions to universities, migration, and job employments [31]. IELTS exam measures test-takers' performance to use English in communicative contexts.…”
Section: Ielts Writingmentioning
confidence: 99%
“…There is now an existing body of research on international student experiences suggesting that, for many, the transition and adjustment to meet local needs of an unfamiliar higher education course is a challenging and multifaceted endeavor (Andrade, 2009;Banerjee, 2003;Clark, 2018). Those entering higher education are expected to develop their academic English skills from the course outseta significant undertaking in some cases, particularly for academic writing (Clark & Yu, 2020). Implications for the study experience of attempting to do this while improving English language proficiency, building peer networks, overcoming financial difficulties and managing cultural adjustment are not to be underestimated (Khanal & Gaulee, 2019).…”
Section: Introductionmentioning
confidence: 99%